High-Throughput Absolute Quantification Sequencing Revealed Osteoporosis-Related Gut Microbiota Alterations in Han Chinese Elderly - Wei, Muhong; Li, Can; Dai, Yu; Zhou, Haolong; Cui, Yuan; Zeng, Yun; Huang, Qin; Wang, Qi (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Accumulative evidence suggests that gut microbiota play an important role in bone remodeling and hence bone health maintenance. This study aimed to explore the association of gut microbiota with the risk of osteoporosis and to identify potential disease-related taxa, which may be promising targets in osteoporosis prevention and treatment in the future. Methods: Absolute quantification 16S ribosomal RNA gene sequencing was used to detect absolute and relative abundances of gut microbiota in 44 patients with osteoporosis and 64 controls. In combination with one of our previous studies, a total of 175 samples were involved in the relative abundance analysis. Results: Compared with the controls, the patients with osteoporosis had higher absolute and relative abundances of Bacteroidetes phylum, and Bacteroides and Eisenbergiella genera. The absolute abundances of Clostridium_XlVa, Coprococcus, Lactobacillus, and Eggerthella genera increased, and that of the Veillonella genus decreased in the osteoporosis group. As for relative abundance, that of the Parabacteroides and Flavonifractor genera increased, whereas that of the Raoultella genus decreased in the osteoporosis group. Controlling for potential confounders, the associations of Clostridium_XlVa, Coprococcus, and Veillonella genera with the risk of osteoporosis did not maintain significance. Ridge regression analysis suggested that Bacteroides is associated with reduced bone mineral density (BMD) and T-score at lumbar spines, and Anaerovorax is associated with increased BMD at the femoral neck. Functional predictions revealed that 10 Kyoto Encyclopedia of Genes and Genomes pathways were enriched in the osteoporosis group. Conclusions: Gut microbiota compositions may contribute to the risk of osteoporosis. Several specific taxa and functional pathways are identified to associate with reduced bone density, thus providing epidemiologic evidence for the potential role of aberrant gut microbiota in osteoporosis pathogenesis.